Fabrication and application of hollow ZnO nanospheres in antimicrobial casein‐based coatings. Issue 2 (17th December 2016) - Liu, Junli; Hui, Aiping; Ma, Jianzhong; Chen, Zhuping; Peng, Yi
Abstract: ZnO hollow nanospheres with porous shells were prepared successfully via a simple hard‐template method and a calcination process. Then the obtained ZnO hollow nanospheres were encapsulated with mildew‐proof agent and modified by polydopamine. At last, antimicrobial casein‐based coatings were obtained by mixing the drug‐loaded ZnO and casein latex. Antimicrobial testing results revealed casein‐based hollow ZnO/mildew‐proof agent nanocomposite films displayed the better antimicrobial activities, and it still has antimicrobial properties after 1 year.